Innate Immune Recognition: Implications for the Interaction of Francisella tularensis with the Host Immune System - Krocova, Zuzana; Macela, Ales; Kubelkova, Klara (Frontiers in Cellular and Infection Microbiology, 2017)
The intracellular bacterial pathogen Francisella tularensis causes serious infectious disease in humans and animals. Moreover, F. tularensis, a highly infectious pathogen, poses a major concern for the public as a bacterium classified under Category A of bioterrorism agents. Unfortunately, research has so far failed to develop effective vaccines, due in part to the fact that the pathogenesis of intracellular bacteria is not fully understood and in part to gaps in our understanding of innate immune recognition processes leading to the induction of adaptive immune response. Recent evidence supports the concept that immune response to external stimuli in the form of bacteria is guided by the primary interaction of the bacterium with the host cell. Based on data from different Francisella models, we present here the basic paradigms of the emerging innate immune recognition concept. According to this concept, the type of cell and its receptor(s) that initially interact with the target constitute the first signaling window; the signals produced in the course of primary interaction of the target with a reacting cell act in a paracrine manner; and the innate immune recognition process as a whole consists in a series of signaling windows modulating adaptive immune response. Finally, the host, in the strict sense, is the interacting cell.